The enigma of primary hypertension in childhood - Falkner, Bonita (Frontiers in Cardiovascular Medicine, 2022)
Beginning in the 1970s, hypertension in children and adolescents has been defined as systolic and/or diastolic blood pressure (BP) that is equal to or greater than the 95th percentile of the normal BP distribution in healthy children. The definition of hypertension in adults is based on longitudinal data that links a BP level with an increased risk for subsequent adverse outcomes related to hypertension including heart failure, kidney failure, stroke, or death. The statistical definition of hypertension continues to be used in childhood because there have been no data that link a BP level in childhood with a heightened risk for adverse outcomes in adulthood. Findings from clinical and epidemiologic research have advanced understanding of high BP in childhood. While hypertension in some children can be secondary to underlying kidney, cardiovascular, or endocrine disorder, it is now known that primary (essential) hypertension can be present in childhood. The prevalence of hypertension in childhood is approximately 2–5% and another 13–18% of children and adolescents have elevated BP and are at heightened risk for developing hypertension. The leading cause of childhood hypertension is primary hypertension, especially in adolescents. For children and adolescents with secondary hypertension, the treatment can focus on managing the underlying cause of hypertension. Less is known about managing primary hypertension in childhood, including diagnosis, evaluation, treatment, and possibilities for prevention. The phenotype of primary hypertension in childhood and recent findings will be discussed.